Pure red cell aplasia caused by D-penicillamine treatment of rheumatoid arthritis. - Tishler, M (1991)
A 40 year old woman with rheumatoid arthritis developed pure red cell aplasia after treatment with D-penicillamine 500 mg/day. D-Penicillamine was stopped and short term treatment with steroids resulted in complete recovery of bone marrow.